2012
DOI: 10.1007/s00417-012-2120-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of retinal layers and visual rehabilitation after epiretinal membrane removal

Abstract: Compared with the postoperative improvement in visual acuity, the postoperative improvement in metamorphopsia was a rather slow process. Parafoveal INL thickness was found to be a significant structural factor for visual acuity and metamorphopsia in ERM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
64
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 40 publications
15
64
1
8
Order By: Relevance
“…Previous studies reported good surgical outcomes and many prognostic factors, such as preoperative visual acuity, retinal thickness, photoreceptor layer status, and the status of other specific layers of the retina, for the outcome following ERM surgery [13,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32]. Among these, preoperative vision is a well-known prognostic factor that influences postoperative vision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported good surgical outcomes and many prognostic factors, such as preoperative visual acuity, retinal thickness, photoreceptor layer status, and the status of other specific layers of the retina, for the outcome following ERM surgery [13,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32]. Among these, preoperative vision is a well-known prognostic factor that influences postoperative vision.…”
Section: Discussionmentioning
confidence: 99%
“…Vision loss by primary ERM effects, such as opacity of the fibrous membrane and deformation of the retina, are reversible after surgical removal at early stages. However, as ERM progresses, secondary degenerative changes affect multiple retinal layers from the ganglion cells to the photoreceptor layers [23,24,25,26,27]. Vision loss by these degenerative changes may be irreversible [25,26,28].…”
Section: Discussionmentioning
confidence: 99%
“…В ряде работ при анализе толщины отдельных слоев сетчатки выявлена взаимосвязь с таким характерным сим-птомом иЭРМ, как М [13,15,17,18]. Максимум толщины внутреннего ядерного слоя (ВЯС) достоверно различался у пациентов с иЭРМ с отсутствием М и пациентов с иЭРМ с локальными и обширными М [13].…”
Section: морфофункциональная характеристика изменений сетчатки у пациunclassified
“…При анализе отдельных слоев сетчатки и их связи с изменением остроты зрения получены данные о взаимо-связи между МКОЗ и максимальной толщиной ВЯС и НЯС [17,18]. В работах других авторов острота зрения коррелирует с толщиной ВЯС только в случае целостно-сти слоя контакта внутренние сегменты/наружные сег-менты (ВС/НС) [13,15].…”
Section: морфофункциональная характеристика изменений сетчатки у пациunclassified
See 1 more Smart Citation